How to Lead an Academic Social Network. - Davidson, Cathy N. (Public Humanities, 2025)
Dubbed "the world's first and oldest academic social network" by a grant reviewer at the National Science Foundation, HASTAC (Humanities, Arts, Science, and Technology Alliance and Collaboratory or "Haystack") built its first interactive website in 2002. Now, 22 years later, HASTAC has some 18,000 network members, over 400 institutional members, and a thriving graduate-student-led HASTAC Scholars program that selects 100 new student members each year. Co-Director Cathy N. Davidson co-founded HASTAC with David Theo Goldberg and numerous other scholars in the humanities and social sciences working in tandem with computer scientists and programmers. Before Wikipedia, Facebook, or Twitter (now X), HASTAC created an open-access, public network with the purpose of making full use of evolving affordances of technology while also critiquing and seeking to improve issues of access, ethics, gender and racial bias, and social and environmental impact. This essay details what it takes to lead and sustain a dues-free, participatory social network with community standards and collaborative decision-making, and where any network member is invited to blog, post, start dialogues, and lead research initiatives, across institutional and other boundaries.